2022
DOI: 10.33271/mining16.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat supply with maintaining a safe mine water level during operation of open geothermal systems in post-coalmining areas

Abstract: Purpose. Evaluation of the efficiency of open geothermal systems in flooded and drained mines of the Donetsk basin for heat supply of buildings with maintaining a safe mine water level. Methods. Both circulation and non-return geothermal systems for the mine water heat recovery are analyzed. We proposed the energy and cost criteria for evaluating the effectiveness of open geothermal systems based on a comparison of the produced thermal energy with the energy costs for its production. The criteria use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to Ref. [ 21 ] and based on the mechanism analysis, the wellhead temperature signal features are extracted from the heat loss during a stroke. Specifically, three features are obtained from the wellhead temperature signal.…”
Section: The Working Condition Recognition Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. [ 21 ] and based on the mechanism analysis, the wellhead temperature signal features are extracted from the heat loss during a stroke. Specifically, three features are obtained from the wellhead temperature signal.…”
Section: The Working Condition Recognition Modelingmentioning
confidence: 99%
“…Moreover, semi-supervised learning (SSL) schemes based on p -Laplacian manifold regularization and loss function significantly enhance the classification performance by utilizing richer unlabeled data efficiently in fewer labeled data [ 19 , 20 ]. Other studies have shown that in practical engineering, data feature analysis combined with expert knowledge and mechanism analysis contributes to more efficient and practical model building [ 21 ]. In summary, combined with the actual operation of the oil well, a working condition recognition method based on measured multisource nonlinear kernel learning and p -Laplacian manifold learning is proposed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Hai Pu et al proposed a method to develop mine geothermal resources with the use of water storage and heat storage in abandoned mines [42]. Rudakov D et al evaluated the efficiency of open geothermal systems in flooded and drained mines for the heat supply of buildings and proved the good effect of the system [43].…”
Section: Mine Geumentioning
confidence: 99%
“…The water inrush coefficient method [27,28] is used to predict whether the floor of the working face is prone to water inrush events [29]. A water inrush coefficient less than 0.06 indicates that the working face is safe; relatively, water inrush may occur when the water inrush coefficient exceeds 0.06 [30,31]. The water inrush coefficients T1max and T2max of the NO.…”
Section: Water-rich Evaluation and Data Acquisitionmentioning
confidence: 99%